Clinical significance of pulmonary hypertension in patients with constrictive pericarditis. Issue 20 (20th July 2021) - Lim, Kyunghee; Yang, Jeong Hoon; Miranda, William R; Chang, Sung-A; Jeong, Dong Seop; Nishimura, Rick A; Schaff, Hartzell; Soo, Wern Miin; Greason, Kevin L; Oh, Jae K
Abstract : Objectives: We investigated haemodynamics and clinical outcomes according to type of pulmonary hypertension (PH) in patients with constrictive pericarditis (CP). Background: As the prevalence of CP with concomitant myocardial disease (mixed CP) grows, PH is more commonly seen in patients with CP. However, haemodynamic and outcome data according to the presence or absence of PH are limited. Methods: 150 patients with surgically confirmed CP who underwent echocardiography and cardiac catheterisation within 7 days at two tertiary centres were divided into three groups: no-PH, isolated postcapillary PH (Ipc-PH) and combined postcapillary and precapillary PH (Cpc-PH). Primary outcome was all-cause mortality during follow-up. Result: In this retrospective cohort study, 110 (73.3%) had PH (mean pulmonary artery pressure ≥25 mm Hg). Cpc-PH, using defined cut-offs for pulmonary vascular resistance (>3 Wood units) or diastolic pulmonary gradient (≥7 mm Hg), was seen in 18 patients (12%). The Cpc-PH group had a higher prevalence of comorbidities (diabetes and atrial fibrillation) and concomitant myocardial disease as an aetiology of CP than other groups. Pulmonary vascular resistance had a significant direct correlation with medial E/e′ by Doppler echocardiography ( r =0.404, p<0.001). Survival rate was significantly lower in the Cpc-PH than the no-PH (p=0.002) and Ipc-PH (p=0.024) groups. On multivariable analysis, age, New York Heart Association functional class IV, medial e′ velocity, Cpc-PH and Ipc-PH were independently associated with long-term mortality. Conclusion: Combined postcapillary and precapillary PH develops in a subset of patients with CP and is associated with long-term mortality after pericardiectomy.